Zeitstrukturen von Kampfhandlungen im Ringen - Ulbricht, H. J.; Bering, A. (Leipziger Sportwissenschaftliche Beiträge, 2012)
Duration and distribution of straight attacks in greco-roman wrestling effect a specific physical strain in competition. There are no studies about the diversifi-cation depending from type and rate during a given fight. Even an imagined differentiation between weight categories was not examined. Determined by use of modified video analysis there are notable varieties in the frequency of attacks. 48 % of the attacks with maximal strength need less than 5 and 41 % less than 10 seconds. The included 94 % total contest time episodes among aerobic requirements are used for a rapid degradation of lactate.